Ethyl Ferulate, a Component with Anti-Inflammatory Properties for Emulsion-Based Creams - Nazare, Ana C. [UNESP]; Faria, Carolina M. Q. G. de [UNESP]; Chiari, Bruna G. [UNESP]; Petronio, Maicon S. [UNESP]; Regasini, Luis O. [UNESP]; Silva, Dulce Helena Siqueira [UNESP]; Correa, Marcos A. [UNESP]; Isaac, Vera L. B. [UNESP]; Fonseca, Luiz M. da [UNESP]; Ximenes, Valdecir F. [UNESP] (Mdpi Ag, 2014)
Ethyl ferulate (FAEE) has been widely studied due to its beneficial heath properties and, when incorporated in creams, shows a high sun protection capacity. Here we aimed to compare FAEE and its precursor, ferulic acid (FA), as free radical scavengers, inhibitors of oxidants produced by leukocytes and the alterations in rheological properties when incorporated in emulsion based creams. The cell-free antiradical capacity of FAEE was decreased compared to FA. However, FAEE was more effective regarding the scavenging of reactive oxygen species produced by activated leukocytes. Stress and frequency sweep tests showed that the formulations are more elastic than viscous. The viscoelastic features of the formulations were confirmed in the creep and recovery assay and showed that the FAEE formulation was less susceptive to deformation. Liberation experiments showed that the rate of FAEE release from the emulsion was slower compared to FA. In conclusion, FAEE is more effective than FA as a potential inhibitor of oxidative damage produced by oxidants generated by leukocytes. The rheological alterations caused by the addition of FAEE are indicative of lower spreadability, which could be useful for formulations used in restricted areas of the skin.
Keywords: neutrophil; NADPH oxidase; oxidative stress; ferulic acid; ethyl ferulate; cosmetic product